Effects of different arginine/lysine level on growth performance, body composition and digestive enzyme activity of Macrobrachium rosenbergii. (9th January 2018) - Dong, X. J.; Wu, J.; Shen, Y.; Chen, J. Y.; Miao, S. Y.; Zhang, X. J.; Sun, L. S.
Abstract: Given the universal presence of antagonism between arginine and lysine, determining the optimal dietary arginine/lysine level is of great importance. In this study, eight diets were formulated to contain different arginine/lysine level, followed by a 9‐week feeding trial with shrimps of 2.10 ± 0.01 cm in length and 0.38 ± 0.02 g in weight to determine the effect of dietary arginine/lysine level on growth performance, body composition and enzyme activity. The results showed that the Diet 6 (arginine/lysine level of 29.4/21.0 g/kg) group had significantly higher weight gain rate, and specific growth rate than the control group and most of the other groups ( p  <   .05) did. Similarly, the retention efficiency of arginine and lysine in the Diet 6 group was significantly higher than the control group and most of the other groups ( p  < .05). Moreover, most digestive enzymes had higher activity levels in the Diet 6 group, and evident antagonism between dietary arginine and lysine was detected. In summary, dietary arginine/lysine level of 29.4/21.0 g/kg produced the best growth performance, suggesting that a better growth performance in Macrobrachium rosenbergii culture can be obtained by adjusting the dietary arginine/lysine level.